Comparative study of antioxidant defence mechanisms in marine fish fed variable levels of oxidised oil and vitamin E - Tocher, Douglas R; Mourente, Gabriel; Van der Eecken, Anne; Evjemo, Jan Ove; Diaz, Esther; Wille, Mathieu; Bell, J Gordon; Olsen, Yngvar (Springer, 2003)
The aim of the study was to compare the antioxidant systems in juvenile marine fish of commercial importance in European aquaculture, namely turbot (Scophthalmus maximus), halibut (Hippoglossus hippoglossus) and gilthead sea bream (Sparus aurata). The present dietary trial was specifically designed to investigate the antioxidant effects of vitamin E under moderate oxidising conditions, including high dietary levels of highly unsaturated fatty acids and the feeding of oxidised oils. The objective was to induce a stressful pro-oxidant status to enable characterisation of the biochemical responses to peroxidative stress without causing unnecessary suffering to the experimental animals or high mortalities during the trials. Both sea bream and turbot showed excellent growth, whereas growth was poorer in halibut. Dietary oxidised oil significantly reduced growth in turbot and especially in halibut, but not in sea bream. Vitamin E improved growth in sea bream fed oxidised oil but not in turbot or halibut. However, vitamin E supplementation appeared to improve survival in all three species. In sea bream and turbot, liver antioxidant defence enzyme activities were generally increased by feeding peroxidised oil and reduced by vitamin E. Conversely, in halibut, the liver antioxidant defence enzyme activities were not increased by feeding peroxidised oil and only superoxide dismutase was reduced by feeding vitamin E. Consistent with these data, feeding oxidised oil increased lipid peroxidation products in halibut, but generally not in sea bream or turbot. Furthermore, lipid peroxidation products were generally reduced by dietary vitamin E in both sea bream and turbot, but not in halibut. Therefore, halibut liver antioxidant defence enzymes did not respond to dietary oxidised oil or vitamin E as occurred in turbot and, especially sea bream. This resulted in increased levels of lipid peroxides in halibut compared to turbot and sea bream in fish given dietary oxidised oil. In addition, supplemental vitamin E did not reduce ...